Redox cycling induces spermptosis and necrosis in stallion spermatozoa while the hydroxyl radical (OH) only induces spermptosis. (17th August 2017) - Martín Muñoz, P; Anel‐López, L; Ortiz‐Rodríguez, JM; Álvarez, M; de Paz, P; Balao da Silva, C; Rodríguez Martinez, H; Gil, MC; Anel, L; Peña, FJ; Ortega Ferrusola, C
Contents: Oxidative stress is a major factor explaining sperm dysfunction of spermatozoa surviving freezing and thawing and is also considered a major inducer of a special form of apoptosis, visible after thawing, in cryopreserved spermatozoa. To obtain further insights into the link between oxidative stress and the induction of apoptotic changes, stallion spermatozoa were induced to oxidative stress through redox cycling after exposure to 2‐methyl‐1, 4‐naphthoquinone (menadione), or hydroxyl radical formation after FeSO4 exposure. Either exposure induced significant increases ( p  < 0.05) in two markers of lipid peroxidation: 8‐iso‐PGF2α and 4‐hydroxynonenal (4‐HNE). While both treatments induced changes indicative of spermptosis (caspase‐3 activation and decreased mitochondrial membrane potential) ( p  < 0.01), menadione induced sperm necrosis and a dramatic reduction in motility and thiol content in stallion spermatozoa. Thus, we provided evidence that oxidative stress underlies spermptosis, and thiol content is a key factor for stallion sperm function.